Abdominal localization unicentric form Castleman disease - Case report - Milev, Boško; Milev, Borka; Kostić, Zoran; Mirković, Darko; Perišić, Nenad; Tasić, Olga; Elez, Marija; Radunović, Aleksandar; Jovanović, Milan; Marić, Predrag; Daišević, Sanja; Perelević, Rade; et al. (Vojnosanitetski pregled, 2017)
Introduction. Castleman disease is a rare disease of the unknown etiology, occuring in two clinical forms: unicentric or multicentric form. It is characterized by the hyperplasia of lymph glands. In references the four pathohistological forms were described: hyaline vascular type, plasma-cell type, mixed type and recently recognized plasmablastic type. Changes are often localized in the mediastinum while in other parts of the body their incidence is less. Case report. At a man of 41, at MR enterography the change was noticed in the ileocecal area without the presence of subjective sympthoms of digestive tract and without loss of body mass. Due to the suspicion of stromal tumor, the surgical intervention was indicated. Pathohistological findings showed - Castelman lymphadenopathia reactiva mesenterii (plasma-cell type) which was in the unicentric form. There were only present the anaemia and increased value of sedimentation from the laboratory analyses. Conclusion. Abdominal localization of the unicentric plasma-cell form has a slight incidence, and surgical method of treatment represents the gold standard as it it was shown in our case.